2014
DOI: 10.1007/s12192-014-0505-8
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of mRNA processing factors TIA-1, TIAR, and PABP-1 during mammalian hibernation

Abstract: Mammalian hibernators survive low body temperatures, ischemia-reperfusion, and restricted nutritional resources via global reductions in energy-expensive cellular processes and selective increases in stress pathways. Consequently, studies that analyze hibernation uncover mechanisms which balance metabolism and support survival by enhancing stress tolerance. We hypothesized processing factors that influence messenger ribonucleic acid (mRNA) maturation and translation may play significant roles in hibernation. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 46 publications
3
17
0
Order By: Relevance
“…Further to this, when the distribution of poly(A) tail lengths were plotted as a function of torpor bout progression, the distribution pattern was consistent with the binding of poly(A)-binding protein (PABP), indicating a possible role of PABP in mRNA stability, as has been shown in other studies (Bernstein et al 1989;Korner and Wahle 1997). While the interaction between mRNA and PABP-1 has not been fully described, we have also recently suggested a role for PABP-1 as an mRNA stabilizer in hepatocytes of thirteen-lined ground squirrels during deep torpor (Tessier et al 2014). Our data showed that despite no observed changes in the relative expression levels of PABP-1 in nuclear fractions from euthermic versus torpid ground squirrels, RNA binding proteins including PABP-1 and TIA-1/R localized to subnuclear structures during torpor.…”
Section: Mrna Processing and Stabilitysupporting
confidence: 86%
See 4 more Smart Citations
“…Further to this, when the distribution of poly(A) tail lengths were plotted as a function of torpor bout progression, the distribution pattern was consistent with the binding of poly(A)-binding protein (PABP), indicating a possible role of PABP in mRNA stability, as has been shown in other studies (Bernstein et al 1989;Korner and Wahle 1997). While the interaction between mRNA and PABP-1 has not been fully described, we have also recently suggested a role for PABP-1 as an mRNA stabilizer in hepatocytes of thirteen-lined ground squirrels during deep torpor (Tessier et al 2014). Our data showed that despite no observed changes in the relative expression levels of PABP-1 in nuclear fractions from euthermic versus torpid ground squirrels, RNA binding proteins including PABP-1 and TIA-1/R localized to subnuclear structures during torpor.…”
Section: Mrna Processing and Stabilitysupporting
confidence: 86%
“…The presence of these nuclear structures is correlated with reduced metabolic rate and their reversal occurs within a few minutes of arousal, providing a mechanism for the rapid resumption of protein synthesis (Malatesta et al 2001). We have also identified a novel subcellular body during hibernation in thirteen-lined ground squirrels (Tessier et al 2014). This subnuclear body consists of RNA-binding proteins such as TIA-1, TIAR, and PABP-1 which are also markers of cytoplasmic stress granules.…”
Section: Subcellular Compartmentation/localizationmentioning
confidence: 83%
See 3 more Smart Citations